The SAGE handbook of qualitative research ethics - Iphofen, Ron; Tolich, Martin (SAGE Reference, 2018)
"This handbook is a much-needed and in-depth review of the distinctive set of ethical considerations which accompanies qualitative research. This is particularly crucial given the emergent, dynamic and interactional nature of most qualitative research, which too often allows little time for reflection on the important ethical responsibilities and obligations. Contributions from leading international researchers have been carefully organised into six key thematic sections: Part One: Thick Descriptions Of Qualitative Research Ethics, Part Two: Qualitative Research Ethics By Technique, Part Three: Ethics As Politics, Part Four: Qualitative Research Ethics With Vulnerable Groups, Part Five: Relational Research Ethics, Part Six: Researching Digitally. This Handbook is a one-stop resource on qualitative research ethics across the social sciences that draws on the lessons learned and the successful methods for surmounting problems the tried and true, and the new."--Publisher's website.